Monika Brugger / Heimat. - Brugger, Monika; Alandete, Christian (Stuttgart : Arnoldsche, 2009)
juwelen, objecten voor het lichaam, installaties
Engels
Frans
boek
Keywords: Brugger, Monika; 1992 - 2008